Critical review: action research - Aulianda, Mega; Djatmika, Ery Tri; Handayati, Puji (INOVASI, 2021)
Action research aims to solve current practical problems while expanding scientific knowledge. A distinctive feature of action research is that the researcher deliberately conducts an intervention while at the same time studying the effects of the intervention. It involves collaboration with business people in real organizations. This is very different from most other research methods. Researchers who use other research methods usually try not to intervene or interfere. The results of this study are a review of several action research articles with an explanation of the findings of these articles along with the strengths and weaknesses of the research.